PENGARUH PERTUMBUHAN EKONOMI DAN JUMLAH PENDUDUK TERHADAP PENGANGGURAN TERBUKA DI KOTA MATARAM - Nurmawati Nurmawati; Mimi Cahayani (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2021)
This study entitled "The Effect of Economic Growth and Total Population on the Level of Open Unemployment in the City of Mataram". In this study, the researcher tried to analyze how the influence of the variables of economic growth and population on the level of unemployment in Mataram City.This type of research is quantitative research, namely research that aims to determine the effect of independent variables in the form of economic growth variables and population on the level of unemployment in Mataram City from 2012-2019. Based on the results of multiple linear regression analysis using SPSS software, it can be obtained partial and simultaneous regression results, namely the independent variable economic growth and population have a significant effect on the level of unemployment in Mataram, while the test results of the coefficient of determination are 0.677, meaning that the variability of the independent variable is 67 , 7%. Meanwhile, 32.3% is influenced by other variables which are not researched. As for the variables that are not invested, the number of jobs and others